2017
DOI: 10.1039/c6nr07608d
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of a ceria–graphene oxide composite for the efficient removal of arsenic species

Abstract: Arsenic contamination has posed a health risk to millions of people around the world. In this study, we describe a simple and facile one-step hydrothermal synthesis of a ceria-graphene oxide (ceria-GO) composite for the efficient removal of arsenic species. The prepared ceria-GO composite materials exhibited almost complete (over 99.99%) and quick removal of both arsenic species within 0.1 mg L of the initial concentration. The calculated adsorption capacities were 185 mg g for As(iii) and 212 mg g for As(v). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Currently, there are different techniques designed to removed arsenic, including adsorption, which is widely used due to its simplicity of operation and scalability [4]. A wide range of adsorbent material have been used such as iron oxides, activated alumina [5], activated carbon [6] and reduced graphene oxide (rGO) with nanoparticles such as magnetite, ceria, zirconium and zirconium oxide and Fe3O4/MnO2 [7][8][9][10][11][12][13]. These materials have shown maximum adsorption capacities of 14.04 up to 212.33 mg/g for As(III) species (H3AsO3, H2AsO3 − , HAsO3 2− and AsO3 3− ), which are the most dangerous species of As.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are different techniques designed to removed arsenic, including adsorption, which is widely used due to its simplicity of operation and scalability [4]. A wide range of adsorbent material have been used such as iron oxides, activated alumina [5], activated carbon [6] and reduced graphene oxide (rGO) with nanoparticles such as magnetite, ceria, zirconium and zirconium oxide and Fe3O4/MnO2 [7][8][9][10][11][12][13]. These materials have shown maximum adsorption capacities of 14.04 up to 212.33 mg/g for As(III) species (H3AsO3, H2AsO3 − , HAsO3 2− and AsO3 3− ), which are the most dangerous species of As.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) and related materials such as graphene/metal oxide composites have received great attention due to their low cost, easy obtainability and compatibility with various substrates (Nie et al, 2016;Sakthivel et al, 2017). Also, synergistic effects provided by the combination of metal oxides and graphene can improve their catalytic performance compared to the individual metal oxides (Nie et al, 2016;Sakthivel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) and related materials such as graphene/metal oxide composites have received great attention due to their low cost, easy obtainability and compatibility with various substrates (Nie et al, 2016;Sakthivel et al, 2017). Also, synergistic effects provided by the combination of metal oxides and graphene can improve their catalytic performance compared to the individual metal oxides (Nie et al, 2016;Sakthivel et al, 2017). Among these, particularly ZnO (Guo et al, 2016;Nasrollahzadeh et al, 2014) has excelled because of its strong oxidizing power, non-toxic nature, low cost and its catalytic ability in both acidic and basic medium (Huang et al, 2012;Joonwichien et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Results from mass health study revealed that more than 400 people in Bangladesh have lost their life due to arsenic poisoning from 2000 to 2009 and many are still suffering from skin lesions and cancer. 4 The new regulations of Environmental Protection Agency (EPA) in 2001 attuned the standard for arsenic in drinking water from 50 to 10 ppb. 5 This new regulation has embarked severe water contamination through arsenic in the many regions of United State of America (USA) and England.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 Among the several methodologies for decontamination of water, adsorption has been considered as one of the cheapest and frequently used techniques due to its ease of application, higher efficiency and wide availability. 4 There are myriads of adsorbents that have been applied and extensively explored for removal of arsenic ranging from simple form of graphene, activated carbon to transition metal oxides based composites. Among the numerous available adsorbents, rare earth metal oxides are more attractive; particularly cerium oxide based composites enjoy a wide range of applications.…”
Section: ■ Introductionmentioning
confidence: 99%